2024
DOI: 10.1037/bul0000407
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress and externalizing behaviors in childhood and adolescence: A systematic review and meta-analysis.

Irene Tung,
Alison E. Hipwell,
Philip Grosse
et al.

Abstract: Accumulating evidence suggests that psychological distress during pregnancy is linked to offspring risk for externalizing outcomes (e.g., reactive/aggressive behaviors, hyperactivity, and impulsivity). Effect sizes across studies have varied widely, however, due to differences in study design and methodology, including control for the confounding continuation of distress in the postnatal period. Clarifying these inconsistencies is necessary to guide the precision of prevention efforts and inform public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…In contrast, studies in larger samples at older child ages have found no moderation by child sex in the prediction of maternal report of child internalizing at age 4 (N = 1948; Bush et al, 2023); or age 4-13 internalizing (N = 7,944; O' Donnell et al, 2014); or age 8 youth self-report of depression or anxiety (N = 1,389; Noroña-Zhou et al, 2022). The recent metanalysis of maternal distress effects on externalizing (Tung et al, 2023) also found no support for child-sex-specific associations. It is quite possible that biological sex differences may be more important for other child outcomes or for developmental periods, such as adolescence, where pubertal onset and associated hormonal shifts play in important role in the development of mental health (Gunnar et al, 2009).…”
Section: Sex-specific Effects?mentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, studies in larger samples at older child ages have found no moderation by child sex in the prediction of maternal report of child internalizing at age 4 (N = 1948; Bush et al, 2023); or age 4-13 internalizing (N = 7,944; O' Donnell et al, 2014); or age 8 youth self-report of depression or anxiety (N = 1,389; Noroña-Zhou et al, 2022). The recent metanalysis of maternal distress effects on externalizing (Tung et al, 2023) also found no support for child-sex-specific associations. It is quite possible that biological sex differences may be more important for other child outcomes or for developmental periods, such as adolescence, where pubertal onset and associated hormonal shifts play in important role in the development of mental health (Gunnar et al, 2009).…”
Section: Sex-specific Effects?mentioning
confidence: 97%
“…That said, researchers do and should continue to attempt to untangle timing. Notably, the meta-analysis of studies predicting children's externalizing problems revealed that prenatal stress effects on child externalizing did not vary based on type and timing of psychological distress during pregnancy (Tung et al, 2023), although effects were larger for earlier outcome timepoints and greater instability of distress between the pre-and postnatal period was associated with larger effects on children's behavior.…”
Section: Some Key Questions Remaining In Prenatal Stress-transmission...mentioning
confidence: 97%
See 1 more Smart Citation
“…Exposure to high levels of stress during pregnancy is a known risk factor for a wide range of offspring outcomes, including early differences in emotionality and behavioral regulation (MacKinnon et al, 2018; Tung et al, 2023; Van den Bergh et al, 2020). Drawing from the Developmental Origins of Health and Disease theory, growing evidence suggests that frequent exposure to life stressors during pregnancy may be a key pathway through which stress-related health disparities are maintained across generations (Entringer et al, 2015; Lefmann & Combs-Orme, 2014; Lu & Halfon, 2003).…”
Section: Prenatal Stress Resiliencementioning
confidence: 99%